Engaging communities, modeling systems: lessons from system dynamics modeling on maternal health in Texas - Brown, Kyrah K.; Lemke, Michael K.; Robinson, Deneen; Fallah-Fini, Saeideh; Lounsbury, David W.; Lambert, Thanayi; Obasanya, Mercy J.; Kindratt, Tiffany B. (Frontiers in Global Women's Health, 2025)
IntroductionDisparate maternal health outcomes among non-Hispanic Black women stem from intricate, interrelated factors shaped by clinical, social, and structural influences. Traditional approaches often fall short in addressing these complexities, necessitating a shift toward systems thinking and community-driven solutions.Methods and materialsThis paper describes the lessons learned from the implementation of system dynamics group model building (SD GMB) workshops grounded in community-based participatory research (CBPR) principles in two separate projects focused on maternal health among Black women. We recruited 31 diverse stakeholders, including individuals with lived experience, and applied trauma-informed facilitation, wraparound support, and structured systems modeling activities. A descriptive analysis of workshop data was performed to accompany the identified lessons learned.ResultsEvaluation data from surveys and open-ended responses indicated high stakeholder satisfaction, increased capacity to apply systems thinking, and a shift from skepticism to agency. Stakeholders valued the inclusive design, reported meaningful learning, and expressed interest in future engagement. The workshops fostered transformative learning and generated actionable systems insights rooted in community experience.DiscussionThis work demonstrates how SD GMB, when integrated with CBPR, can build trust, elevate marginalized voices, and produce models that reflect structural realities. Future directions include quantifying the models, hosting learning labs to test interventions, and developing an open-access dashboard to simulate policy scenarios. These findings contribute to ongoing efforts to design more engaging, community-informed approaches to maternal health research and practice.